Incidence of Chips Positive Carcinoma of Prostate following Turp for Clinically Benign Prostatic Hyperplasia Patients with Normal Serum PSA (Bangladesh Journal of Urology, 2012)
A cross sectional study was performed to evaluate the frequency of chips positive carcinoma of prostate following TURP for clinically benign prostatic hyperplasia patient with normal serum PSA. A total of 250 patients were initially screened & 100 patients were included into the study according to the selection & exclusion criteria. They were evaluated by using IPSS, a physical examination including DRE & neurological examination to exclude any neurological deficit & neurologically related bladder dysfunction. The prostate was next assessed by transabdominal US. Serum PSA level was then measured & at a cut off value of < 4 ng/ml were enrolled in this study. In our study only 2 patients were found having adenocarcinoma. Therefore incidence of carcinoma prostate in clinically BPH patients with normal s. PSA is low. Low incidence in present series revealed the usefulness of s.PSA screening method. To avoid unusual systemic needle biopsy for diagnostic purpose s.PSA measurement should be done. Bangladesh Journal of Urology, Vol. 14, No. 1, January 2011 p.14-18